2011
DOI: 10.1590/s1677-04202011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phytoaccumulation of Arsenic and Chromium on Structural and Ultrastructural Changes of Brake Fern (Pteris vittata)

Abstract: structural and ultrastructural changes caused by bioaccumulation of as and cr in brake fern (Pteris vittata), a known arsenic hyperaccumulator, were investigated. Potted plants of brake fern were exposed to metal treatments of as and cr for three weeks. leaf, stem and root samples were collected periodically and fixed for lM (light Microscopy), seM (scanning electron Microscopy) and teM (transmission electron Microscopy) to evaluate anatomical changes. the fresh weights, dry weights, rWc (relative Water conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…However, the determination of the quantity and quality of these compounds required to improve As resistance will need further studies. Sridhar et al (2011) observed clumpy deposits on the roots and stem of As-contaminated Pteris vittata, a hyperaccumulating fern. The authors suggested these deposits could be related to a detoxification mechanism.…”
Section: Resultsmentioning
confidence: 89%
“…However, the determination of the quantity and quality of these compounds required to improve As resistance will need further studies. Sridhar et al (2011) observed clumpy deposits on the roots and stem of As-contaminated Pteris vittata, a hyperaccumulating fern. The authors suggested these deposits could be related to a detoxification mechanism.…”
Section: Resultsmentioning
confidence: 89%
“…According to Sridhar et al (2011) andDe Temmerman et al (2004), species that are sensitive to pollutants translocate low amounts of them to the shoots when compared to hyperaccumulator ones. In addition to the low arsenic amounts that were detected in the shoots, the studied species presented anatomical alterations and growth decrease.…”
Section: Speciesmentioning
confidence: 99%
“…As is released from both natural sources (parent rocks) and also from various anthropogenic activities such as agricultural practices, irrigation with As-contaminated water (Waqas et al, 2015), the improper applications of arsenical fertilizers, insecticides, herbicides, use of poultry litter with As-based intestinal palliatives (Jia et al, 2012; Oti, 2015; Zhu et al, 2008), mining activities, and petroleum refineries (Martínez-Sánchez et al, 2011; Khan et al, 2014; Kabata-Pendias, 2011). Soil is a major sink of As, which can lead to contamination of vegetables because of its high mobility and uptake rate (Sridhar et al, 2011). The bioavailability of As and its subsequent bioaccumulation in vegetables (tomato, cucumber, cauliflower, pea, lettuce, spinach, cabbage, onion, radish, turnip, carrot, potato, etc) depend on soil texture, pH, organic matter content and composition, redox condition, water regime, mineral composition, and microbial activity (e.g., Bergqvist et al, 2014; Khan et al, 2015a; Smith et al, 2009).…”
Section: Introductionmentioning
confidence: 99%